Optimization of Islamic Religious Education in Economic Empowerment of the People in Padangsidimpuan Hutaimbaru District - Rhama Lenasari; Aisahrani Ritonga; Dewi Candra; Zulhimma Zulhimma (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
Islamic religious education not only functions to shape the faith and morals of students, but also has a strategic role in encouraging independence and economic empowerment of the community. This study aims to analyze the role of Islamic religious education in Padangsidimpuan District. Hutaimbaru , Contribution of economic empowerment to the Hutaimbaru community , as well as supporting and inhibiting factors of economic empowerment for the Hutaimbaru community . This study uses a qualitative approach with descriptive methods. The research subjects include religious leaders, educators or instructors of Islamic Religious Education, community leaders, and micro-entrepreneurs who were selected purposively based on their involvement in religious and economic activities. Data collection was conducted through in-depth interviews, field observations, and documentation as supporting data. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions, with data validity maintained through triangulation techniques. The results of the study indicate that Islamic religious education plays a role in instilling the values of hard work, honesty, responsibility, and entrepreneurial spirit which are the foundation for strengthening the people's economy. Optimization is carried out through religious studies, religious guidance, social preaching, and strengthening Islamic economic values in everyday life. Obstacles faced include limited capital, low business skills, and less than optimal sustainable mentoring. Therefore, synergy is needed between educational institutions, religious leaders, and the government to strengthen the economic empowerment of the people based on Islamic values.